EFFECTIVENESS OF WORK TRAINING IMPLEMENTATION THAT IMPACT TO IMPROVING PERFORMANCE OF EMPLOYEES - Budi Santoso, Anton; Oktafien, Shinta (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze and measure to what extent the influence of job training on employee performance in the Environmental Department of Majalengka Regency. The population in this study is the total number of employees who work in the Department of the Environment of Majalengka Regency, with a total of 72 people. Meanwhile, for the number of research samples taken in this study, as many as 61 respondents used a sampling technique in the form of cluster random sampling. The research method used in this study is a survey research method for which data processing and analysis techniques are used in the form of simple regression analysis. The results of his research indicate that job training has a significant effect on employee performance in the Environmental Department of Majalengka Regency. Thus, it is said that the more effective job training that is held at an organization or company, the higher the work results that can be shown by the employees that are included in connection with increasingly increasing the work ability of employees at work.